2005
DOI: 10.1177/204748730501200103
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Intensity Modalities of Resistance Training on Beat-to-Beat Blood Pressure in Cardiac Patients

Abstract: The SBP and HR responses to resistance training are related to the duration of exercise. Sets with < or =10 repetitions of high intensity should be preferred to longer sets with low intensity. Pauses between exercise sets should exceed 1 min. Blood pressure should be measured during the last repetitions of the exercise set.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(31 citation statements)
references
References 33 publications
1
27
0
2
Order By: Relevance
“…There may be a relationship between the time under tension (6 RM = 17 ± 3 s versus 12 RM = 29 ± 5 s) and such results. This possibility confirms the results reported by Lamotte et al 17 , who analyzed the effect of the execution of leg extension exercise in a leg extension machine, with workloads equivalent to 40% and 70% of an RM (4 sets with one-minute interval between sets), on the responses of HR and BP in patients with heart disease. The sets involving the intensity of 40% lasted 34s on average (for 17 repetitions) against 20s of the set done with 70% of the maximum workload (for 10 repetitions).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…There may be a relationship between the time under tension (6 RM = 17 ± 3 s versus 12 RM = 29 ± 5 s) and such results. This possibility confirms the results reported by Lamotte et al 17 , who analyzed the effect of the execution of leg extension exercise in a leg extension machine, with workloads equivalent to 40% and 70% of an RM (4 sets with one-minute interval between sets), on the responses of HR and BP in patients with heart disease. The sets involving the intensity of 40% lasted 34s on average (for 17 repetitions) against 20s of the set done with 70% of the maximum workload (for 10 repetitions).…”
Section: Discussionsupporting
confidence: 90%
“…At the end of each set, the values of SBP and DBP always proved to be significantly higher than the ones observed in the previous sets. Other studies have demonstrated that there is influence of the number of sets on cardiovascular responses 2,17 . Two factors may be in the origin of the results referring to the cumulative effect of consecutive sets on cardiovascular responses.…”
Section: Discussionmentioning
confidence: 95%
“…The rMSSD and SD1 indexes reflect the vagal modulation of HR (9,22,28). The progressive decrease in this index beginning at 30% 1RM in both groups can be explained by a decrease in parasympathetic modulation and, consequently, a predominance of sympathetic modulation at higher intensities (6).…”
Section: Discussionmentioning
confidence: 99%
“…However, at higher intensities, sympathetic tonus continues to predominate and results in increased HR and blood pressure until the end www.bjournal.com.br Braz J Med Biol Res 44 (12) 2011 of the exercise (6,8). A marked increase in blood pressure response has been observed during RE, in contrast to dynamic exercise (9,10). The increase in blood pressure occurs during repetitions, but if the exercise is not sustained, there will be a return to baseline conditions.…”
mentioning
confidence: 99%
“…Dessa forma protocolos incrementais pode ser interessante, uma vez que podem determinar a magnitude das respostas fisiológicas (principalmente lactato sanguíneo ([La]) e VO2) em diferentes domínios (leve, moderado e alto), pois através deles é possível identificar parâmetros de aptidão aeróbia e anaeróbia, como o limiar de lactato (LL), limiar de lactato (LA), limiar de lactato individual (LAI), lactato mínimo (LM), limiar de compensação respiratório (RCT), limiar glicêmico (LG), máxima fase estável de lactato (MFEL) e potência crítica (PC) ou carga crítica (CC) (Lamotte, Niset e Van De Borne, 2005), sendo que essas ferramentas são aplicáveis ao exercício dinâmico e que a pouco tempo elas tem sido exploradas em exercício resistido.…”
Section: Avaliação Para Determinar a Intensidade Do Treinamento Resisunclassified